Chloride solid electrolyte, preparation method thereof and battery
By constructing a high entropy structure and alloying interface, the preparation of lanthanide UCl3 type metal chlorides by liquid phase method is solved, and the problems of low conductivity and high cost are achieved, efficient lithium ion migration and interface stability are achieved, suitable for large-scale application.
Patent Information
- Application Number
- CN202411477818.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2024-12-17
AI Technical Summary
The ionic conductivity of the lanthanide UCl3 type metal chloride solid electrolyte is generally low, the electrochemical window is narrow, and the material preparation cost is high, which limits its large-scale commercial application.
By introducing metal cations of different radii, the high-entropy structure lanthanide UCl3 type metal chloride is constructed, and the liquid phase method is prepared, combined with doping of a variety of low-cost elements, the alloying interface is constructed to improve lithium ion migration and interface stability.
It significantly improves the room temperature ionic conductivity of lanthanide UCl3 metal chloride, broadens the electrochemical window, reduces the cost of material preparation, is suitable for large-scale industrial production, and improves the stability of the interface between lithium anode and electrolyte.
Smart Images

Figure BDA0005096577680000071 
Figure BDA0005096577680000081
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy batteries, and in particular to a chloride solid electrolyte, a preparation method thereof, and a battery. Background Art
[0002] With the widespread application of lithium-ion batteries in portable electronic devices and electric vehicles, people have paid extensive attention to the safety issues caused by the inherent disadvantages of organic liquid electrolytes, such as flammability, volatility and poor heat resistance. Compared with organic electrolytes, all-solid-state batteries use non-flammable solid electrolytes instead of electrolytes and diaphragms, which fundamentally eliminates the safety hazards brought by liquid electrolytes, greatly improves the safety of batteries, and prolongs the service life of batteries. At present, inorganic solid electrolytes mainly include oxide solid electrolytes, sulfide solid electrolytes and halide solid electrolytes. Oxide solid electrolytes have good electrochemical oxidation stability, but their ion conductivity still needs to be further improved. In addition, the preparation process of oxide electrolytes usually requires a high sintering temperature, and their inherent hard and brittle characteristics will lead to very large mass transfer impedance at the interface between the positive and negative electrodes. Although sulfide electrolytes have good plasticity and high ionic conductivity, the electrochemical window of sulfide electrolytes is narrow and the electrochemical compatibility with positive electrode materials is poor. They are also very sensitive to moisture and can react with trace water in the air to produce toxic gases. Chloride solid electrolyte materials have unique anion chemical properties and take into account the performance advantages of metal oxides and metal sulfides, and can achieve a good balance between interface stability and ionic conductivity. However, there is still a need to further improve ionic conductivity and broaden the electrochemical window. At present, chloride electrolytes are mainly prepared by methods such as high-energy ball milling and high-temperature melting. However, the above operation steps are too cumbersome and energy-consuming to be easily developed on a large scale.
[0003] UCl3-type metal chlorides have large one-dimensional channels rich in lithium ion transmission, which can be occupied by lithium ions and provide fast migration sites, which is beneficial to reduce the barrier of lithium ion migration and has attracted great attention from researchers. Lanthanide UCl3-type metal chlorides currently still have low conductivity at room temperature and high material preparation costs, which hinder the large-scale commercial application of lanthanide UCl3-type metal chloride solid electrolytes. How to combine a simple preparation method with low-cost raw materials to prepare lanthanide UCl3-type metal chlorides is of great significance for the large-scale development and application of halide electrolytes. Summary of the invention
[0004] In view of this, the present invention is committed to providing a chloride solid electrolyte and a preparation method and battery thereof, so as to solve the problems in the prior art that the lanthanide UCl3 type metal chloride ions generally have low electrical conductivity, narrow electrochemical window and high material preparation cost.
[0005] In order to solve the above technical problems, this application is implemented as follows:
[0006] A first aspect of the present invention provides a chloride solid electrolyte, the chloride solid electrolyte comprising Li a M b Fe c La d Cl3, wherein M is selected from at least one of Al, Ce, Zr, Mg, Cr and Ca, wherein 0 <a≤0.4,0<b≤0.75,0<c≤0.167,0<d≤0.167。
[0007] Optionally, M includes P and Q, wherein P is selected from Al and / or Ca, and Q is selected from at least one of Ce, Zr, Mg and Cr.
[0008] Optionally, the chloride solid electrolyte includes Li 0.4 Al 0.2 Fe 0.167 La 0.167 Cr 0.167 Ce 0.167 Cl3、Li 0.4 Zr 0.2 Fe 0.167 La 0.167 Cr 0.167 Al 0.1 Cl3、Li 0.4 Zr 0.2 Fe 0.167 La 0.167 Ce 0.167 Al 0.1 Cl3 and Li 0.4 Mg 0.275 Fe 0.167 La 0.167 Ce 0.167 Ca 0.275 At least one of Cl3.
[0009] Optionally, the D50 of the chloride solid electrolyte is 20-50 μm.
[0010] A second aspect of the present invention provides a method for preparing the chloride solid electrolyte, the method comprising the following steps:
[0011] S1, mixing LiCl, aqueous chloride of element M, FeCl3·6H2O and LaCl3·6H2O with a solvent to obtain a first material;
[0012] S2, drying the first material to obtain a precursor;
[0013] S3, grinding the precursor;
[0014] Wherein, M is selected from at least one of Al, Ce, Zr, Mg, Cr and Ca.
[0015] Optionally, the solvent is water.
[0016] Optionally, in step S1, the mixing is mechanical mixing, and the conditions of the mechanical mixing include: a rotation speed of 100 to 500 rpm and a time of 5 to 10 min.
[0017] Optionally, in step S2, the drying treatment conditions include: a temperature of 90 to 120° C. and a time of 6 to 12 hours.
[0018] Optionally, in step S3, the grinding treatment is a dry ball milling treatment, and the conditions of the dry ball milling treatment include: a rotation speed of 400 to 600 rpm and a time of 4 to 10 min.
[0019] A third aspect of the present invention provides a battery, the battery comprising a solid electrolyte, the electrolyte comprising the above-mentioned chloride solid electrolyte and / or the chloride solid electrolyte prepared according to the above-mentioned method.
[0020] Through the above technical solution, the beneficial technical effects of the present invention are:
[0021] (1) The present invention constructs a high entropy structure lanthanide UCl3-type metal chloride by introducing metal cations of different radii, introduces local lattice distortion, thereby promoting rapid migration of lithium ions and improving the oxidation stability of the metal chloride solid electrolyte.
[0022] (2) The present invention uses a liquid phase method to prepare a lanthanide UCl3 type metal chloride solid electrolyte, which greatly shortens the preparation time and has a low reaction temperature, making it suitable for large-scale industrial production. The halide is evenly distributed in the liquid phase, and it is easier to obtain a sample with uniform grain size after crystallization.
[0023] (3) The present invention is beneficial to improving the interface stability between the lithium negative electrode / metal chloride solid electrolyte and reducing the interface impedance by constructing an alloying interface.
[0024] (4) The solid electrolyte of the present invention contains abundant reserves of elements such as Al, La, Ce, Fe, Zr, Mg, Cr, and Ca, and has the advantages of low cost and feasibility of large-scale mass production.
[0025] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION
[0026] The present invention discloses a chloride solid electrolyte and a preparation method and a battery. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar replacements and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0027] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0028] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0029] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0030] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0031] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0032] In order to solve the problems in the prior art that the lanthanide UCl3 type metal chloride ions generally have low electrical conductivity, narrow electrochemical window, and high material preparation cost, the present invention adopts the following technical solution:
[0033] A first aspect of the present invention provides a chloride solid electrolyte, the chloride solid electrolyte comprising Li a M b Fe c La d Cl3, wherein M is selected from at least one of Al, Ce, Zr, Mg, Cr and Ca, wherein 0 <a≤0.4,0<b≤0.75,0<c≤0.167,0<d≤0.167。
[0034] The chloride solid electrolyte of the present invention constructs a high entropy structure lanthanide UCl3-type metal chloride by introducing metal cations of different radii, and introduces local lattice distortion to promote rapid migration of lithium ions and improve the oxidation stability of the metal chloride solid electrolyte.
[0035] According to the present invention, in order to further promote the rapid migration of lithium ions and improve the oxidation stability of the metal chloride solid electrolyte, M may include P and Q, wherein P is selected from Al and / or Ca, and Q is selected from at least one of Ce, Zr, Mg and Cr. Preferably, Q is selected from two or more elements of Ce, Zr, Mg and Cr.
[0036] In a preferred embodiment of the present invention, the chloride solid electrolyte may include Li 0.4 Al 0.2 Fe 0.167 La 0.167 Cr 0.167 Ce 0.167 Cl3、Li 0.4 Zr 0.2 Fe 0.167 La 0.167 Cr 0.167 Al 0.1 Cl3、Li 0.4 Zr 0.2 Fe 0.167 La 0.167 Ce 0.167 Al 0.1 Cl3 and Li 0.4 Mg 0.275 Fe 0.167 La 0.167 Ce 0.167 Ca 0.275 At least one of Cl3.
[0037] According to the present invention, the D50 of the chloride solid electrolyte may be 20 to 50 μm. Exemplarily, the D50 of the chloride solid electrolyte may be any value among 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm and 50 μm or any value within the range of any two of the above values.
[0038] A second aspect of the present invention provides a method for preparing the chloride solid electrolyte, the method comprising the following steps:
[0039] S1, mixing LiCl, aqueous chloride of element M, FeCl3·6H2O and LaCl3·6H2O with a solvent to obtain a first material;
[0040] S2, drying the first material to obtain a precursor;
[0041] S3, grinding the precursor;
[0042] Wherein, M is selected from at least one of Al, Ce, Zr, Mg, Cr and Ca.
[0043] The preparation method of the chloride solid electrolyte of the present invention combines the advantages of a liquid phase method with low-cost doping of metal elements of various valence states to construct a high-entropy metal chloride solid electrolyte, achieving a higher ionic conductivity (>1mS / cm) of the lanthanide UCl3-type metal chloride solid electrolyte at room temperature, which not only expands the lanthanide UCl3-type metal chloride electrolyte family system, but also can exert good electrochemical properties, and its preparation process is relatively simple, and no organic solvent is added, which is relatively friendly to the environment, has the advantage of low cost and is conducive to large-scale production.
[0044] According to the present invention, the solvent may be water.
[0045] The mixing ratio of LiCl, the aqueous chloride of element M, FeCl3.6H2O and LaCl3.6H2O in the present invention can be mixed according to the chemical formula of the target compound.
[0046] In one embodiment of the present invention, in step S1, in order to mix the raw materials uniformly, the mixing is mechanical mixing, and the conditions of the mechanical mixing may include: a rotation speed of 100 to 500 rpm and a time of 5 to 10 min.
[0047] In one embodiment of the present invention, in step S2, the drying conditions may include: a temperature of 90 to 120° C. and a time of 6 to 12 hours.
[0048] In one embodiment of the present invention, in step S3, the grinding process may be a dry ball milling process, and the conditions of the dry ball milling process may include: a rotation speed of 400 to 600 rpm and a time of 4 to 10 min.
[0049] A third aspect of the present invention provides a battery, the battery comprising a solid electrolyte, the electrolyte comprising the above-mentioned chloride solid electrolyte and / or the chloride solid electrolyte prepared according to the above-mentioned method.
[0050] The present invention is further described in detail by way of examples. The raw materials used in the examples can be obtained through commercial sources.
[0051] Example 1
[0052] 4mmol LiCl, 2mmol AlCl3·6H2O, 1.67mmol FeCl3·6H2O, 1.67mmol LaCl3·6H2O, 1.67mmol CrCl3·6H2O and 1.67mmol CeCl3·6H2O were weighed in molar ratio, and added to a beaker filled with deionized water, and mechanically mixed until completely dissolved to obtain a first material, wherein the speed of mechanical mixing was 400rpm, and the time was 180min; the first material was placed in a vacuum drying oven and heated and dried at a low temperature of 120°C for 6h, and after the deionized water was completely volatilized, a precursor was obtained, which was dry-milled at a speed of 600rpm for 6h and then sieved to obtain the chloride solid electrolyte Li of this embodiment. 0. 4Al 0.2 Fe 0.167 La 0.167 Cr 0.167 Ce 0.167 Cl3, the D50 of the solid electrolyte of this embodiment is 46μm.
[0053] Example 2
[0054] The preparation method of the solid electrolyte in this embodiment is the same as that in Example 1, except that the raw materials in this embodiment are 4mmolLiCl, 1mmolAlCl3·6H2O, 1.67mmolFeCl3·6H2O, 1.67mmolLaCl3·6H2O, 1.67mmolCrCl3·6H2O and 2mmolZrCl4·6H2O, and the chemical formula of the obtained chloride solid electrolyte is Li 0.4 Zr 0.2 Fe 0.167 La 0.167 Cr 0.167 Al 0.1 Cl3.
[0055] Example 3
[0056] The preparation method of the solid electrolyte in this embodiment is the same as that in Example 1, except that the raw materials in this embodiment are 4mmolLiCl, 1mmolAlCl3·6H2O, 1.67mmolFeCl3·6H2O, 1.67mmolLaCl3·6H2O, 1.67mmolCeCl3·6H2O and 2mmolZrCl4·6H2O, and the chemical formula of the obtained chloride solid electrolyte is Li 0.4 Zr 0.2 Fe 0.167 La 0.167 Ce 0.167 Al 0.1 Cl3.
[0057] Example 4
[0058] The preparation method of the solid electrolyte in this embodiment is the same as that in Example 1, except that the raw materials in this embodiment are 4mmol LiCl, 2.75mmol MgCl2·6H2O, 1.67mmol FeCl3·6H2O, 1.67mmol LaCl3·6H2O, 1.67mmol CeCl3·6H2O and 2.75mmol CaCl2·6H2O, and the chemical formula of the obtained chloride solid electrolyte is Li 0.4 Mg 0.275 Fe 0.167 La 0.167 Ce 0.167 Ca 0.275 Cl3.
[0059] Example 5
[0060] The preparation method of the solid electrolyte in this embodiment is the same as that in Example 1, except that the raw materials in this embodiment are 4mmolLiCl, 2mmolZrCl4·6H2O, 2mmolAlCl3·6H2O, 1.67mmolFeCl3·6H2O and 1.67mmolLaCl3·6H2O, and the chemical formula of the obtained chloride solid electrolyte is Li 0.4 Zr 0.2 Al 0.2 Fe 0.167 La 0.167 Cl3.
[0061] Example 6
[0062] The preparation method of the solid electrolyte in this embodiment is the same as that in Example 1, except that the raw materials in this embodiment are 4mmol LiCl, 4mmol ZrCl2·6H2O, 1.67mmol FeCl3·6H2O and 1.67mmol LaCl3·6H2O, and the chemical formula of the obtained chloride solid electrolyte is Li 0.4 Zr 0.4 Fe 0.167 La 0.167 Cl3.
[0063] Comparative Example 1
[0064] 3.84mmol LiCl, 2.616mmol FeCl3 and 6.104mmol LaCl3 were weighed in molar ratio and added to a ball mill. After being well sealed, dry ball milling reaction was performed. The ball-to-material ratio was 40:1. A 100mL ball mill was selected, the ball milling speed was 500rpm, and the ball milling time was 4h. The chemical formula of the chloride solid electrolyte material obtained after ball milling is Li 0.384 Fe 0.2616 La 0.6104 Cl3.
[0065] Test Example 1
[0066] The AC impedance test is carried out by an electrochemical workstation, and the mold symmetrical battery to be assembled is composed of stainless steel / electrolyte material / stainless steel. The specific test steps are as follows: First, weigh a certain mass (for example, 200 mg) of electrolyte material under an inert atmosphere and place it in a mold battery with a diameter of 10 mm. Subsequently, the electrolyte material is cold pressed into a disc with a diameter of 10 mm at a pressure of 350 MPa and the pressure is maintained for 30 seconds. The thickness of the electrolyte is measured using a high-precision vernier caliper and recorded as L. The temperature for conventional ionic conductivity testing is 25°C, and the calculation formula is σ=L / (R*S), where L is the thickness of the solid electrolyte disc after cold pressing, S is the electrolyte area after cold pressing, and R is the impedance of the electrolyte material measured by the AC impedance method. The ionic conductivity of the electrolyte is calculated, and the test results are shown in Table 1.
[0067] The calculation method of configuration entropy is Smix = -RΣ i x i lnx i Where: R is the gas constant; x i is the molar content of the ith element in the component. The calculation results are shown in Table 1.
[0068] Table 1
[0069]
[0070] Test Example 2
[0071] The solid electrolytes of each embodiment and comparative example were prepared to obtain batteries. The specific preparation method includes: in an argon glove box, the positive electrode active material nickel cobalt manganese ternary positive electrode material (NCM811) and the chloride solid electrolyte material were weighed at a mass ratio of 80:20 and then ground to obtain a composite positive electrode material. In a solid-state battery mold with a diameter of 10 mm, 20 mg of the above-mentioned composite positive electrode material and 100 mg of chloride solid electrolyte material were stacked. Then the two layers were pressurized at a pressure of 350 MPa, and the negative electrode used a lithium sheet with a diameter of 10 mm and a thickness of 100 μm as the negative electrode, and was pressurized at a low pressure of 100 MPa. The mold battery shell screws were tightened to obtain a full solid-state battery. The assembled solid-state battery was tested for cycle performance. The test conditions are: current density of 0.2C, voltage range of 2.5-4.3V. The test results are shown in Table 2.
[0072] The test method for the first week discharge capacity includes: the battery cell is subjected to constant current charge and discharge test, at a rate of 0.2C, the voltage range is 2.5-4.3V. The specific operation is: discharge at a constant current to 2.5V at a current density of 0.2, and record the charge capacity at this time as the first charge capacity.
[0073] The test method of the first week coulomb efficiency includes: charging the battery cell at a constant current of 0.2C to 4.3V, recording the charging capacity at this time as the first charging capacity; discharging at a constant current of 0.2C to 2.5V, recording the discharge capacity at this time as the first discharge capacity. First week coulomb efficiency = first discharge capacity / first charge capacity*100%.
[0074] The test method for the 100-week discharge capacity retention rate includes: the battery cell is first discharged at a constant current of 0.2C to 2.5V, and the discharge capacity at this time is recorded as the first discharge capacity. After 100 weeks, the battery cell is discharged at a constant current of 0.2C to 2.5V, and the discharge capacity at this time is recorded as the discharge capacity after 100 weeks. 100-week discharge capacity retention rate = discharge capacity after 100 weeks / first discharge capacity*100%.
[0075] Table 2
[0076]
[0077] Test Example 3
[0078] In an argon glove box, the solid electrolytes prepared in each embodiment and comparative example were tested for their interfacial compatibility with lithium metal anodes and their ability to inhibit lithium dendrites. A symmetrical button cell with the structure of Li / solid electrolyte material to be tested / Li was assembled for constant current cycling test. 2The cycle test was carried out under the surface current of , and the cycle stability time (the occurrence of voltage polarization is used as the instability criterion) was shown in Table 3.
[0079] Among them, the method of constant current cycle test includes: first weigh 120mg of Li6PS5Cl solid electrolyte powder, put it into a battery mold, and cold press the electrolyte powder into a ceramic sheet (Φ=10mm) under a pressure of 250MPa. Then, two pieces of metal lithium negative electrodes (Φ=8mm) are attached to both sides of the ceramic sheet, and the battery is packaged under a pressure of 25MPa. The prepared lithium symmetrical battery is charged and discharged at a certain current density, and the voltage-time curve is recorded to evaluate the stability of the lithium negative electrode interface and the dendrite growth in the battery.
[0080] Table 3
[0081] Group Symmetrical battery stable cycle time (h) Example 1 493 Example 2 542 Example 3 452 Example 4 360 Example 5 374 Example 6 392 Comparative Example 1 320
[0082] It can be seen from the data in Tables 1 to 3 that the solid electrolyte of the present invention can significantly improve the cycle stability of all-solid-state lithium metal batteries. Specifically, compared with Comparative Example 1, the lanthanide UCl3-type metal chloride solid electrolyte of the present invention has significantly improved configurational entropy and ionic conductivity; at the same time, the first-week discharge capacity, first-week coulomb efficiency and 100-week discharge capacity retention rate of the all-solid-state battery prepared by using the chloride solid electrolyte of Examples 1 to 6 are all improved; the stable cycle time of the button symmetrical battery prepared by using the chloride solid electrolyte of Examples 1 to 6 is extended; especially when M in the chloride solid electrolyte selects at least three elements (Examples 1 to 4), the improvement effect of each performance test is more significant. The method of the present invention uses a simple liquid phase method and utilizes heterovalent metal cations of a variety of low-cost elements to dope the lanthanide UCl3-type metal chloride solid electrolyte to obtain a high-entropy metal chloride solid electrolyte with high ionic conductivity, and greatly improves its interface stability with the lithium negative electrode.
[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A chloride solid electrolyte, characterized in that: The chloride solid electrolyte includes Li a M b Fe c La d Cl3, wherein M is selected from at least one of Al, Ce, Zr, Mg, Cr and Ca, 0 <a≤0.4,0<b≤0.75,0<c≤0.167,0<d≤0.167。 2. The chloride solid electrolyte according to claim 1, characterized in that M includes P and Q, wherein P is selected from Al and / or Ca, and Q is selected from at least one of Ce, Zr, Mg and Cr.
3. The chloride solid electrolyte according to claim 1, characterized in that The chloride solid electrolyte includes Li 0.4 Al 0.2 Fe 0.167 La 0.167 Cr 0.167 Ce 0.167 Cl3、Li 0.4 Zr 0.2 Fe 0.167 La 0.167 Cr 0.167 Al 0.1 Cl3、Li 0.4 Zr 0.2 Fe 0.167 La 0.167 Ce 0.167 Al 0.1 Cl3 and Li 0.4 Mg 0.275 Fe 0.167 La 0.167 Ce 0.167 Ca 0.275 At least one of Cl3.
4. The chloride solid electrolyte according to claim 1, characterized in that The D50 of the chloride solid electrolyte is 20 to 50 μm.
5. A method for preparing the chloride solid electrolyte according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: S1, mixing LiCl, aqueous chloride of element M, FeCl3·6H2O and LaCl3·6H2O with a solvent to obtain a first material; S2, drying the first material to obtain a precursor; S3, grinding the precursor; Wherein, M is selected from at least one of Al, Ce, Zr, Mg, Cr and Ca.
6. The method according to claim 5, characterized in that The solvent is water.
7. The method according to claim 5, characterized in that In step S1, the mixing is mechanical mixing, and the conditions of the mechanical mixing include: a rotation speed of 100 to 500 rpm and a time of 5 to 10 minutes.
8. The method according to claim 5, characterized in that In step S2, the drying conditions include: a temperature of 90 to 120°C and a time of 6 to 12 hours.
9. The method according to claim 5, characterized in that In step S3, the grinding process is a dry ball milling process, and the conditions of the dry ball milling process include: a rotation speed of 400 to 600 rpm and a time of 4 to 10 minutes.
10. A battery, characterized in that: The battery comprises a solid electrolyte, wherein the electrolyte comprises the chloride solid electrolyte according to any one of claims 1 to 4 and / or the chloride solid electrolyte prepared according to the method according to any one of claims 5 to 9.
